The effect of breaking sitting time with physical activity breaks on cognitive performance in young people with cerebral palsy: an exposure response cross-over feasibility design - Coe Shelly; Cossington Jo; Collett Johnny; Meaney Andy; Mavrommati Foteini; Ng Yujun; Izadi Hooshang; Wade Will; Pindus Dominika M.; Bushnell Oliver; Whaymand Luke; Theologis Tim; et al. (Translational Exercise Biomedicine)
To assess the feasibility of methods and estimate the potential effect of interrupting sedentary behaviour, with intermittent or continuous physical activity breaks, on cognitive performance in young people with Cerebral Palsy.